(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
The study analyzed access to commercial bank credit by rural farmers in Enugu State, Nigeria. Three specific objectives guided the study. Purposive and random sampling techniques were employed to select 80 rural farmers for the study. Primary data were collected with the use of well-structured questionnaire through the aid of trained data collection agents. Descriptive and inferential statistics such as Ordinary Least Square (OLS) Regression and Access Index models were used for data analysis. A greater percentage (46.9%) of the studied farmers was between 20-40 years, 35.8% was between 41 - 60 years, while 17.3% was 60 years and above. Level of education, membership of cooperative societies, farming experience and value of asset held by farmers facilitated access to credit. Also, result shows that high interest rate, inadequate collateral and communication problem between commercial banks and farmers were the major constraints hindering access to credit.